Lung Abscess as a Delayed Complication in a COVID-19 Pneumonia Patient: A Case Report - Indah Rahmawati; Regia Anadhia Pinastika; Raditya Bagas Wicaksono (Faculty of Medicine Universitas Airlangga, 2022)
Introduction: In March 2020, the World Health Organization (WHO) proclaimed coronavirus disease 2019 (COVID-19) a global pandemic. Indonesia is one of the nations that is still dealing with the COVID-19 outbreak. COVID-19 has several complications, including lung abscesses in extremely rare cases. We presented the first reported COVID-19 patient in Indonesia with a delayed lung abscess. Case: A 30-year-old man presented to the hospital with breathlessness and tested positive for COVID-19. Chest X-ray revealed typical COVID-19 pneumonia. He was discharged after 16 days of hospitalization and was educated on using oxygen at home lest the breathlessness recurred. We planned to evaluate the patient’s chest X-ray after 2 weeks of discharge. The follow-up chest X-ray revealed an air-fluid level in the upper lobe of the right lung, indicating a lung abscess. The patient was treated with antibiotics for 2–3 weeks. Clinical follow-up 4 weeks after the treatment revealed no symptoms, and chest X-ray showed significant improvement. Conclusion: Lung abscess is one of the rare complications of COVID-19. A pulmonary infection creates an air-fluid level by forming a cavity in the lung parenchyma. Notably, this complication manifested 2 weeks after the patient was discharged. COVID-19 can have several unexpected complications, including lung abscesses. It is crucial to monitor patients after discharge for such complications, especially if they are symptomatic.